Examining The Impact of Liquidity And Solvency Ratios on Firm’s Profitability: Insights From The Indonesian Tech Companies - Miranda tanjung (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Indonesia's technological landscape has undergone a swift transformation, marked by rapid innovation, digitalization, and a surge in technology companies seeking to capitalize on emerging markets and opportunities. Purpose: This paper explores the relationships between solvency ratio, liquidity ratio, and profitability ratios (ROA and ROE) within the context of technology companies in Indonesia. Design/Methodology: This quantitative study uses datasets of 35 technology companies in the IDX. The datasets were collected from OSIRIS and publicly available data relevant to the tech companies in Indonesia. The analysis period is from 2018 to 2022.Results: Based on the data analysis, we found that solvency ratios correspond only to better profitability ratios. Therefore, the study fills a research gap by identifying a positive correlation between solvency ratios and ROA, indicating that moderate debt levels can enhance profitability through leverage. This study also highlights the financial characteristics of the tech sector, underscoring the importance of industry-specific analysis.Conclusion: The research finds that the lack of a direct relationship between current ratios and profitability in Indonesian tech firms may arise due to the firms’ capital-intensive nature, reliance on intangible assets, and prioritization of growth and innovation over short-term liquidity. Originality: This study explored financial metrics in Indonesia's tech firms, highlighting their structures with high capital investment and intangible assets. Examining solvency and liquidity ratios' impact on profitability offers insights for stakeholders better to assess financial health in this fast-growing industry in Indonesia. Keywords: financial performance, liquidity, ROE, solvency ratio, tech company, profitability